Cannabis use during pregnancy and hemodynamic responses to infant cues in pregnancy: an exploratory study - Powers, Shannon; Han, Xu; Martinez, Jacqueline; Dufford, Alexander John; Metz, Torri D.; Yeh, Tom; Kim, Pilyoung (Frontiers in Psychiatry, 2023)
Introduction Cannabis is one of the most commonly used substances during pregnancy and has the potential to negatively impact parent-infant relationships.1 The prefrontal cortex (PFC) response to infant cues during pregnancy has been associated with subsequent positive parenting behaviors. However, PFC activation is altered in individuals who use cannabis.2 As the potency of cannabis has changed over the years, little is known about the specific role of cannabis use on gestational parent brain responses to infant cues. Materials and Methods Using functional Near-Infrared Spectroscopy (fNIRS) in the second trimester of pregnancy, we measured hemodynamic responses to an infant cry task and an infant faces task among individuals who were using cannabis (N=14) and compared them with those who were not using cannabis (N=45). For the infant cry task, pregnant individuals listened to cry sounds and matched white noise. For the infant faces task, they viewed happy, sad, and neutral faces. Results There was no significant difference between the two groups after adjusting for multiple comparisons. Without adjusting for multiple comparisons, we found preliminary evidence for the differences in the dorsomedial PFC associated with heightened response to infant cry among individuals who use cannabis. The groups were also different in the dorsolateral PFC associated with decreased response to infant sad faces among individuals who use cannabis. Discussion Our preliminary data suggests that cannabis use during pregnancy was associated with brain activation in the regions involved in the emotional regulation and information processes. However, the results did not survive after adjustment for multiple comparisons, thus future research with larger sample sizes is needed to confirm potential differences in brain function among cannabis-using pregnant individuals.